Regulation of Executive Compensation at Nonprofit Health Care Organizations: Coming Changes? - David Albert Bjork (SAGE Publishing, 2010)
Executive compensation in health care organizations, particularly tax-exempt organizations, has come under increasing scrutiny in recent years. This paper identifies the implications for tax-exempt health care organizations of recent efforts to regulate executive pay, as well as some changes that the boards of nonprofit health care providers and insurers should consider to minimize the case for further scrutiny and regulation of their executive pay practices.